2023
DOI: 10.1159/000528974
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Blood Supply in Germany: A Regulatory Perspective

Abstract: <b><i>Background and Objectives:</i></b> A sufficient supply of safe, high-quality blood components for transfusion is essential to the healthcare system in Germany. The requirements for the current reporting system are laid down in the German Transfusion Act. The present work elaborates on the advantages and limitations of the current reporting system and investigates the feasibility of a pilot project that collects specific data on blood supply based on weekly reports. <b><i&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…All manuscripts published within the focus topic “Blood Supply and Blood Safety” in this issue of Transfusion Medicine and Hemotherapy deals with partial aspects of the abovementioned WHO activities in one way or another. Fiedler et al [ 3 ] reported from a regulatory perspective about the necessity of a nation-wide monitoring not only of blood donations but also of blood consumptions and at best blood inventories at blood establishments and hospitals in order to anticipate blood shortages (e.g., due to crisis such as COVID-19 pandemic) and to initiate measures to manage those blood shortages reasonably and timely (e.g., regional compensation by exchange, postpone elective surgery). Samukange et al [ 4 ] summarize the activities of BloodTrain funded by the German Ministry of Health.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…All manuscripts published within the focus topic “Blood Supply and Blood Safety” in this issue of Transfusion Medicine and Hemotherapy deals with partial aspects of the abovementioned WHO activities in one way or another. Fiedler et al [ 3 ] reported from a regulatory perspective about the necessity of a nation-wide monitoring not only of blood donations but also of blood consumptions and at best blood inventories at blood establishments and hospitals in order to anticipate blood shortages (e.g., due to crisis such as COVID-19 pandemic) and to initiate measures to manage those blood shortages reasonably and timely (e.g., regional compensation by exchange, postpone elective surgery). Samukange et al [ 4 ] summarize the activities of BloodTrain funded by the German Ministry of Health.…”
mentioning
confidence: 99%
“…Blood Supply and Blood Safety" in this issue of Transfusion Medicine and Hemotherapy deals with partial aspects of the abovementioned WHO activities in one way or another. Fiedler et al[3] reported from a regulatory perspective about the necessity of a nation-wide monitoring…”
mentioning
confidence: 99%
“…However, the amount of currently stored blood products is not available in real time. Fiedler et al [ 2 ] examined the number of whole blood donations from 2009 to 2021 and explored the feasibility of a weekly reporting system. The authors observed that the number of whole blood donations decreased from 4.86 million in 2009 to 3.67 million in 2020 and 3.7 million in 2021.…”
mentioning
confidence: 99%
“…Using a weekly monitoring approach, Fiedler et al [ 2 ] assessed the number of RBC unit stocks and analyzed the supply sufficiency, which was defined as a reserve of RBC units for three or more days. The authors showed that relative to the total number of RBC units, the share of blood type O and RhD positive RBC units fluctuated between 35% and 22% and for O and RhD negative RBC units between 17% and 5%.…”
mentioning
confidence: 99%
See 1 more Smart Citation